Pharmacokinetic properties of the temozolomide perillyl alcohol conjugate (NEO212) in mice. Issue 1 (20th November 2020) - Cho, Hee-Yeon; Swenson, Steve; Thein, Thu Zan; Wang, Weijun; Wijeratne, Neloni R; Marín-Ramos, Nagore I; Katz, Jonathan E; Hofman, Florence M; Schönthal, Axel H; Chen, Thomas C
Abstract: Background: NEO212 is a novel small-molecule anticancer agent that was generated by covalent conjugation of the natural monoterpene perillyl alcohol (POH) to the alkylating agent temozolomide (TMZ). It is undergoing preclinical development as a therapeutic for brain-localized malignancies. The aim of this study was to characterize metabolism and pharmacokinetic (PK) properties of NEO212 in preclinical models. Methods: We used mass spectrometry (MS) and modified high-performance liquid chromatography to identify and quantitate NEO212 and its metabolites in cultured glioblastoma cells, in mouse plasma, brain, and excreta after oral gavage. Results: Our methods allowed identification and quantitation of NEO212, POH, TMZ, as well as primary metabolites 5-aminoimidazole-4-carboxamide (AIC) and perillic acid (PA). Intracellular concentrations of TMZ were greater after treatment of U251TR cells with NEO212 than after treatment with TMZ. The half-life of NEO212 in mouse plasma was 94 min. In mice harboring syngeneic GL261 brain tumors, the amount of NEO212 was greater in the tumor-bearing hemisphere than in the contralateral normal hemisphere. The brain:plasma ratio of NEO212 was greater than that of TMZ. Excretion of unaltered NEO212 was through feces, whereas its AIC metabolite was excreted via urine. Conclusions: NEO212 preferentially concentrates in brain tumor tissue over normal brain tissue, and compared to TMZ has a higher brain:plasma ratio, altogether revealing favorable features to encourage its further development as a brain-targeted therapeutic. Its breakdown into well-characterized, long-lived metabolites, in particular AIC and PA, will provide useful equivalents for PK studies during further drug development and clinical trials with NEO212.